EVOLUTION AND REVOLUTION: SECONDARY SCHOOL CHANGES FOR ONTARIO AND QUEBEC - McCall, Douglas S. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1982)
That Quebec is not a province like the others should be apparent in many ways. In education the sheer scale of the undertaking to develop the system, and with it in due course society as a whole, seems little appreciated even within Quebec, and yet there are few parallels to it in the world. McCall compares two apparently similar documents of reform of the secondary system, in Quebec and in Ontario - its massive and confident neighbour - and shows that the real differences between them are far-ranging and have an ideological base; though whether that is because two different ideologies are at work, or only one, may be a question. RÉSUMÉ Il est manifeste à bien des égards que le Québec n’est pas une province comme les autres. En éducation, l’importance de l’engagement à développer le système, et avec lui, en temps voulu, toute la société, semble mal comprise même au Québec et pourtant, il existe peu de situations parallèles dans le monde. McCall compare deux documents de réforme du système secondaire apparemment analogues au Québec et en Ontario, (son voisin massif et plein d’assurance) et démontre que les véritables différences entre les deux sont multiples et ont toutes une base idéologique; que cela soit dû au fait qu’il y ait deux idéologies différentes en jeu, ou seulement une, reste à prouver.